2015
DOI: 10.1021/acsmedchemlett.5b00296
|View full text |Cite
|
Sign up to set email alerts
|

Trioxolane-Mediated Delivery of Mefloquine Limits Brain Exposure in a Mouse Model of Malaria

Abstract: Peroxidic antimalarial agents including the sequiterpene artemisinins and the synthetic 1,2,4-trioxolanes function via initial intraparasitic reduction of an endoperoxide bond. By chemically coupling this reduction to release of a tethered drug species it is possible to confer two distinct pharmacological effects in a parasite-selective fashion, both in vitro and in vivo. Here we demonstrate the trioxolane-mediated delivery of the antimalarial agent mefloquine in a mouse malaria model. Selective partitioning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…Uptake in the brain was very low, consistent with previous observations that other TRX conjugates do not cross the blood–brain barrier. 31…”
Section: Resultsmentioning
confidence: 99%
“…Uptake in the brain was very low, consistent with previous observations that other TRX conjugates do not cross the blood–brain barrier. 31…”
Section: Resultsmentioning
confidence: 99%
“…Our design of ICL-1 involved caging D-luciferin with a 1,2,4-trioxolane scaffold (51) used previously for in vivo delivery of therapeutic payloads in an Fe 2+ -dependent manner (50,54). The excellent pharmacokinetic properties of these therapeutic conjugates suggested that ICL-1 would have suitable in vivo properties for the desired imaging applications.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we demonstrated the utility of the TRX scaffold by efficiently and selectively delivering antimalarial payloads to ferrous iron/heme rich compartments of the malaria parasite, both in vitro 30,31 and in vivo. 32,33 …”
Section: Introductionmentioning
confidence: 99%